Effect of the aqueous solution of "mashua" on the reproductive capacity of male mus musculus and its implication in preimplantation embryonic development. Preclinical test: Efecto de la solucion acuosa de "mashua" en la capacidad reproductiva de mus musculus machos y su implicancia en el desarrollo embrionario preimplantacional. Prueba preclínica - Gonzales-Daga, José (2020)
The "mashua", Tropaeolum tuberosum Ruiz & Pavón, 1802 is a plant species native from Peru and a resource of great nutritional value. In addition, there are several investigations carried out in the last decade in which its effects on mammal fertility have been verified. In this work, we evaluate the effect of the aqueous extract of T. tuberosum on the development of the preimplantation embryos of Mus musculus. The aqueous extract was administered ad libitum, in a concentration of 50 g / Kg of body weight, to three groups of mice (n = 24) during 8, 16 and 35 days; the control group drank only tap water. Each group of males were crossed with females of fertile age, the presence of a vaginal plug indicated the 0th day of embryonic development. At 72 h the uterine horns were perfused and the stage of development, condition and embryonic morphology were evaluated. Differences were found between the control and treatment groups. Our results demonstrate that the aqueous extract of T. tuberosum alters the quality of the mouse sperm, affecting the ability of the embryo to develop normally to the blastocyst stage.